Description of the male of Dendrolycosa cruciata (Roewer, 1955) (Araneae: Pisauridae: Pisaurinae) - Da Silva, Estevam L. Cruz (Zootaxa, 2013)
The spider genus Dendrolycosa Doleschall, 1859 was recently revised by Jäger (2011), who described four new species and now comprises 15 known species found from Tanzania to Phillipines and south to New Caledonia (Platnick 2012). Ten of the 15 Dendrolycosa species are known only from females and two only from males. In the present paper, the male of Dendrolycosa cruciata (Roewer, 1955) is described and illustrated for the first time.